2020
DOI: 10.5114/aoms.2017.69726
|View full text |Cite
|
Sign up to set email alerts
|

Is pentraxin 3 level an effective biomarker in disease activity in patients with rheumatoid arthritis?

Abstract: The aim of the current study was to identify whether serum pentraxin 3 (PTX3) level could be a marker of increased inflammation in rheumatoid arthritis (RA) patients. Material and methods: The study included 41 patients diagnosed with RA according to the American College of Rheumatology (ACR) 1990 diagnostic criteria. We compared the serum PTX3 levels between RA patients and a healthy control group, the relationship between PTX3 level and disease activity was also examined. Results: A statistically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Here, for the first time, we analyzed PTX3 expression profiles in a cohort of early and treatment-naïve RA patients at baseline, and 6-months after cs-DMARD treatment. As previously described, we confirmed that RA patients presented a higher concentration of circulating PTX3 compared to healthy donors (13)(14)(15) and that PTX3 levels positively correlated with CRP (16). In addition, we showed that, at the onset of the disease prior to any treatment modification, circulating PTX3 levels also correlated with ESR, DAS28 and the count of swollen and tender joints, therefore being a strong marker of disease activity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Here, for the first time, we analyzed PTX3 expression profiles in a cohort of early and treatment-naïve RA patients at baseline, and 6-months after cs-DMARD treatment. As previously described, we confirmed that RA patients presented a higher concentration of circulating PTX3 compared to healthy donors (13)(14)(15) and that PTX3 levels positively correlated with CRP (16). In addition, we showed that, at the onset of the disease prior to any treatment modification, circulating PTX3 levels also correlated with ESR, DAS28 and the count of swollen and tender joints, therefore being a strong marker of disease activity.…”
Section: Discussionsupporting
confidence: 88%
“…In the context of RA, PTX3 has been shown to be constitutively highly expressed by synovial fibroblasts (12); however, as described in other tissues, various resident or infiltrating synovial cells like macrophages or endothelial cells might also represent a source of PTX3 upon inflammatory activation. Several groups found that PTX3 is upregulated in the serum of RA patients compared to healthy donors (13)(14)(15) or patients with osteoarthritis (16). However, conflicting results have been published regarding the relationship between the level of PTX3 in the serum and clinical features of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression level of CRP is elevated and regarded as a biomarker in RA (Atzeni et al, 2017;Wasserman, 2018). In RA, the level of PTX3 has been found to be higher than that in the control group (Balbaloglu & Ozcan, 2020). As compared traditional biomarkers, PTX3 has been found to be a sensitive non-invasive biomarker of clinical arthritis activity in RA (Sharma et al, 2018), indicating that ER, CRP and PTX3 may play a significant role in improving arthritis.…”
Section: Discussionmentioning
confidence: 98%
“…However, despite all these symptoms, the presence of IA is the hallmark of clinical diagnosis of RA. The diagnosis criteria is compromised as a series of joint examination and imaging, testing of RA-related autoantibodies, systemic inflammation, and the duration of joint symptoms [1,4].…”
Section: Introductionmentioning
confidence: 99%